Peran Sutradara Pembuatan Video Pendek Sebagai Media Promosi Prodi Ilmu Komunikasi Universitas Dharma Andalas - Rio Idul Permata; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to explore the director’s involvement across pre-production, production, and post-production stages in the promotional video for the Communication Science Study Program at Dharma Andalas University. Using a qualitative descriptive method, the data were collected through observation and documentation. The results show that a successful promotional video relies heavily on directing strategies that harmonize narrative, visuals, and emotional resonance. The director plays a critical role in concept development, talent direction, visual aesthetics, and production coordination to deliver a communicative and engaging video. This study emphasizes the director’s position not only as a technical guide but also as a creative leader translating institutional messages into visual form. Challenges such as equipment limitations, scheduling, and adapting to social media trends can be overcome through innovative directing. The resulting video is expected to enhance the program’s competitiveness among higher education institutions..